Electrical barriers and their elimination by tuning (Zn, Mg)O buffer composition in Cu(In, Ga)S2 solar cells: systematic approach to achieve over 14% power conversion efficiency. (1st October 2022) - Sood, Mohit; Gnanasambandan, Poorani; Adeleye, Damilola; Shukla, Sudhanshu; Adjeroud, Noureddine; Leturcq, Renaud; Siebentritt, Susanne
Abstract: Traditional cadmium sulfide (CdS) buffer layer in selenium-free Cu(In, Ga)S2 solar cells leads to reduced open-circuit voltage because of a negative conduction band offset at the Cu(In, Ga)S2 /CdS interface. Reducing this loss necessitates the substitution of CdS by an alternative buffer layer. However, the substitute buffer layer may introduce electrical barriers in the device due to unfavorable band alignment at the other interfaces, such as between buffer/ZnO i-layer. This study aims to reduce interface recombinations and eliminate electrical barriers in Cu(In, Ga)S2 solar cells using a combination of Zn1− x Mg x O and Al-doped Zn1− x Mg x O buffer and i-layer combination deposited using atomic layer deposition and magnetron sputtering, respectively. The devices prepared with these layers are characterized by current–voltage and photoluminescence measurements. Numerical simulations are performed to comprehend the influence of electrical barriers on the device characteristics. An optimal composition of Zn1− x Mg x O ( x = 0.27) is identified for a suitable conduction band alignment with Cu(In, Ga)S2 with a bandgap of ∼1.6 eV, suppressing interface recombination and avoiding barriers. Optimized buffer composition together with a suitable i-layer led to a device with 14% efficiency and an open-circuit voltage of 943 mV. A comparison of optoelectronic measurements for devices prepared with zinc oxide (ZnO) and Al:(Zn, Mg)O shows the necessity to replace the ZnO i-layer with Al:(Zn, Mg)O i-layer for a high-efficiency device.